Improving comfort level in traffic flow of CACC vehicles at lane drop on two-lane highways - Liu, Huaqing; Jiang, Rui (Physica A, 2021)
This paper studies traffic flow of cooperative adaptive cruise control (CACC) vehicles at lane drop on two-lane highways. A constant time gap algorithm has been used for the upper level longitudinal control of the CACC vehicles. In the control zone upstream of the lane drop, a heuristic control scheme of the CACC vehicles has been used, in which virtual leading vehicle has been introduced by mapping a vehicle on the neighboring lane to the present lane. To improve the passenger comfort, a restriction of the command acceleration caused by virtual leading vehicle, denoted as acmd,lim, has been introduced. It is shown that with the decrease of |acmd,lim|, while the capacity does not change, the comfort of passengers significantly improves.